Stress and catecholamines modulate the bone marrow microenvironment to promote tumorigenesis - Hanns, Pauline (Cell Stress, 2019)
High vascularization and locally secreted factors make the bone marrow (BM) microenvironment particularly hospitable for tumor cells and bones to a preferred metastatic site for disseminated cancer cells of different origins. Cancer cell homing and proliferation in the BM are amongst other regulated by complex interactions with BM niche cells (e.g. osteoblasts, endothelial cells and mesenchymal stromal cells (MSCs)), resident hematopoietic stem and progenitor cells (HSPCs) and pro-angiogenic cytokines leading to enhanced BM microvessel densities during malignant progression. Stress and catecholamine neurotransmitters released in response to activation of the sympathetic nervous system (SNS) reportedly modulate various BM cells and may thereby influence cancer progression. Here we review the role of catecholamines during tumorigenesis with particular focus on pro-tumorigenic effects mediated by the BM niche.